Effects of escitalopram with a Chinese traditional compound Jiuweizhenxin-keli on mismatch negativity and P50 in patients with major depressive disorders - Kuang W; Tian L; Yue L; Li J (Neuropsychiatric Disease and Treatment)
Weihong Kuang,1,* Liantian Tian,2,* Lili Yue,1 Jin Li1 1Department of Psychiatry and Mental Health Center, West China Hospital, Sichuan University, Chengdu, People’s Republic of China; 2Occupational Respiratory Disease Research Center, No 4 West China Hospital/West China School of Public Health, Sichuan University, Chengdu, People’s Republic of China *These authors contributed equally to this work Objective: The objective of this study was to investigate the therapeutic effects of escitalopram in conjunction with Jiuweizhenxin-keli on neuroelectrophysiology in patients with major depressive disorders (MDD).Patients and methods: Patients with depressive episode of MDD according to the criteria of Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, were randomly assigned to Esc group (30 patients) receiving escitalopram treatment and JK group (30 patients) treated with a combination of escitalopram and Jiuweizhenxin-keli. The healthy control (HC) group (30 persons with normal health condition) served as control. All groups were subject to examination of 24-item Hamilton Depression Rating Scale and Hamilton Anxiety Scale, mismatch negativity (MMN), and sensory gating potential P50 (SG-P50) of event-related potentials. Data were collected at three different time points: baseline (before treatment) and week 2 and week 6 post treatment.Results: At baseline, all electrophysiological parameters of patients with MDD were significantly higher than those of HCs. After treatment, in the Esc group, MMN latency, S2-P50 amplitude, and S2-P50/S1-P50 amplitude ratio decreased; however, the decrements were not statistically significant compared to either baseline or the HC group. Also, no significant changes were observed in the percentage of individuals whose S2-P50/S1-P50 ≥0.5 in the Esc group. On the other hand, in the JK group after a 6-week treatment, MMN latency (206.35±32.14 ms) was significantly shorter than that of the Esc group (219.57±36.51 ms), S2-P50 amplitude (7.27±4.85 µV) reduced significantly compared with the baseline level (10.21±4.10 µV), the percentage of individuals whose S2-P50/S1-P50 ≥0.5 in the JK group greatly decreased and this was not significantly different compared to that of the HC group (P≥0.05).Conclusion: Neuroplasticity of patients with MDD is apparently disturbed, characterized by aberrant MMN latency and SG-P50-related event-related potential parameters. A combination of escitalopram and Jiuweizhenxin-keli treatment can markedly restore these neuroelectrophysiological features, and thus, could be a novel therapeutic solution for improving the impaired neuroplasticity of MDD patients. Keywords: major depressive disorder, Jiuweizhenxin-keli, escitalopram, MMN, P50, neuroplasticity